Immunodeficiency-Associated Lymphoid Hyperplasia As a Cause of Intussusception in a Case of Activated PI3K-δ Syndrome - Mettman, Daniel; Thiffault, Isabelle; Dinakar, Chitra; Saunders, Carol (Frontiers in Pediatrics, 2017)
Activated PI3K-Delta Syndrome (APDS) refers to a recently described primary immunodeficiency syndrome consisting of recurrent sinopulmonary infections, lymphadenopathy, mucosal lymphoid aggregates, increased susceptibility to Epstein Barr-virus (EBV) and cytomegalovirus (CMV), and increased incidence of B-cell lymphomas. Variants in PIK3CD, which encodes the phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit delta isoform, enhance membrane association and kinase activity, resulting in increased signal transduction through the PI3K-Akt pathway. Whole-exome sequencing revealed a pathogenic PIK3CD variant in a patient with history of immunologic impairment, recurrent sinopulmonary infections and lymphoid hyperplasia presenting as intussusception. This case illustrates that while lymphoid hyperplasia secondary to immunodeficiency is most often unsurprising and nonthreatening, it can present as an emergency like intussusception.